Humeral surface replacement for osteoarthritis: Outcome related to glenoid erosion. (October 2013) - Smith, Tomas; Gettmann, Andre; Wellmann, Mathias; Pastor, Frederic; Struck, Melena
Abstract : Background and purpose Humeral resurfacing has shown promising results for osteoarthritis, but revisions for glenoid erosion have been reported frequently. We investigated the hypothesis that preoperative glenoid wear and postoperative progress of glenoid erosion would influence the clinical outcome. Methods We reviewed 61 resurfacing hemiarthroplasties (55 patients) for primary osteoarthritis. 6 patients were lost to follow-up and 5 had undergone revision arthroplasty. This left 50 shoulders in 44 patients (mean age 66 years) that were followed for mean 30 (12–44) months. Complications, revisions, and the age- and sex-related Constant score were assessed. Radiographs were evaluated for loosening and glenoid erosion according to Walch. Results Of the 50 shoulders that were functionally assessed, the average age- and sex-related Constant score was 73%. In patients with preoperative type-B2 glenoids, at 49% it was lower than in type-A1 glenoids (81%, p = 0.03) and in type-B1 glenoids (84%, p = 0.02). The average age- and sex-related Constant score for patients with type-A2 glenoids (60%) was lower than for type-A1 and -B1 glenoids and higher than for type-B2 glenoids, but the differences were not statistically significant. In the total population of 61 shoulders, the radiographs showed postoperative glenoid erosion in 38 cases and no humeral prosthetic loosening. Revision arthroplasty was performed in 11 cases after 28 (7–69) months. The implant size had no statistically significant influence on the functional outcome. The size was considered to be adequate in 28 of the 50 functionally assessed shoulders. In 21 cases, the implant size was too large and in 1 case it was too small. Interpretation We found frequent postoperative glenoid erosion and a high rate of revision arthroplasty after humeral resurfacing for primary osteoarthritis. Oversizing of the implants was common, but it had no statistically significant influence on the functional outcome. Inferior results were found in the presence of increased eccentric preoperative glenoid wear. Total shoulder arthroplasty should be considered in these patients.